In Vitro Evaluation of Sunscreens: An Update for the Clinicians. (27th November 2012) - Pelizzo, Maria; Zattra, Edoardo; Nicolosi, Piergiorgio; Peserico, Andrea; Garoli, Denis; Alaibac, Mauro
Abstract : Topical sunscreens contain molecules or molecular complexes that can absorb, reflect, or scatter UV photons. Evaluation of the efficacy of sunscreen products has been made through the Sun Protection Factor (SPF), a mean of quantitatively assessing in vivo the degree of protection offered by sunscreen products against solar radiation. In vivo evaluation of SPF has several drawbacks. First of all, this evaluation method is expensive in terms of money and time. Moreover, it raises several ethical issues concerning the potential damage to skin volunteers. Several in vitro techniques have been developed, but at present there is no broadly accepted method. In this paper, we will discuss some of the recent advances concerning the in vitro evaluation of sunscreens which would be acceptable for replacing in vivo assays.